SPECIFIC SIGNS AND METHODS FOR PREVENTING DRUG ADDICTION AMONG YOUNG PEOPLE (TULA REGION) - Yuliya Borisovna Kinyasheva; Zhanna Olegovna Artemova (Sovremennye Issledovaniâ Socialʹnyh Problem, 2018)
The article considers the drug problem in modern society, which is the most complicated one and dangerous for youth, as the most receptive social group. It is defined, that drug prevention is an important instrument in the reduction of non-medical drug and psychotropic substances consumption. The results of anti-drug policy are affected by a combination of preventing and operational measures together with the total development of the interdepartmental cooperation. The article represents the original summary’s research, written on the basis of studying and theoretical analysis of sources, documents on the research issue, and also data from the report “About the Drug Situation in Tula Region”.